AhR Antagonist Promotes Differentiation of Papillary Thyroid Cancer via Regulating circSH2B3/miR-4640-5P/IGF2BP2 Axis - Sa, Ri; Guo, Meiliang; Liu, Danyan; Guan, Feng (Frontiers in Pharmacology, 2021)
Abnormally high expression of aryl hydrocarbon receptor (AhR) has been implicated in dedifferentiation of radioiodine-refractory papillary thyroid cancer (RR-PTC). This study aimed to evaluate the differentiation effect of AhR antagonist in PTC, and to explore the potential mechanism of it. Results showed that AhR antagonists promoted differentiation of PTC, as shown as increase in 125I uptake and Na/I symporter (NIS) expression level. CircRNA microarray in K1 cells treated with StemRegenin 1(SR1) revealed that hsa_circ_0006741 (circSH2B3) was down-regulated in SR1 treated K1 cells. Downregulation of circSH2B3 increased 125I uptake and NIS expression levels. CircSH2B3 acted as an endogenous sponge of hsa-miR-4640-5p and modulated IGF2BP2 expression. IGF2BP2 overexpression induced dedifferentiation of PTC, while silencing IGF2BP2 accelerated differentiation of PTC cells. Rescue studies showed that the dedifferentiation activity of AhR was modulated by the circSH2B3/miR-4640-5p/IGF2BP2 axis. Our findings confirmed for the first time that AhR antagonists promote differentiation of PTC via inhibiting the circSH2B3/miR-4640-5p/IGF2BP2 axis, offering a novel therapeutic approach and a potential marker for differentiation of PTC.